2021
DOI: 10.1101/2021.11.22.469443
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative transcriptional analysis of the satellite glial cell injury response

Abstract: Satellite glial cells (SGCs) tightly surround and support primary sensory neurons in the peripheral nervous system and are increasingly recognized for their involvement in the development of neuropathic pain following nerve injury. The SGCs are difficult to investigate due to their flattened shape and tight physical connection to neurons in vivo and their rapid changes in phenotype and protein expression when cultured in vitro. Consequently, several aspects of SGC function under normal conditions as well as af… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…This is theorized to occur in order to provide greater metabolic support as neurons go through the costly process of regeneration. However, others, using flow cytometry and single cell sequencing, have found no evidence of proliferation (27,73,87). Jager and colleagues suggested that these BrdU positive cells are likely to be proliferating macrophages that have invaded the neuron-glia unit (87), a phenomenon which has been previously reported (88).…”
Section: Reactive Gliosis: Beyond Gfapmentioning
confidence: 95%
See 3 more Smart Citations
“…This is theorized to occur in order to provide greater metabolic support as neurons go through the costly process of regeneration. However, others, using flow cytometry and single cell sequencing, have found no evidence of proliferation (27,73,87). Jager and colleagues suggested that these BrdU positive cells are likely to be proliferating macrophages that have invaded the neuron-glia unit (87), a phenomenon which has been previously reported (88).…”
Section: Reactive Gliosis: Beyond Gfapmentioning
confidence: 95%
“…A growing body of evidence suggests that SGCs are closely related to Schwann cells and may in fact be immature Schwann cells held in their present state by interactions with sensory neurons (26). Supporting this view, SGCs rapidly change their phenotype in monoculture, becoming less broad and more closely resembling Schwann cells or their precursors, termed sympathoblasts (26,27).…”
Section: Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Under a regular light microscope, SGCs are hardly visible, which has meant that their presence in peripheral neuronal culture systems often goes unnoticed (Thakur et al, 2014). On the other hand, SGCs cultured in the absence of neurons rapidly regress into a Schwann-cell like precursor phenotype (George et al, 2018;Jager et al, 2022), which means that any in vitro studies of pure SGCs have to be undertaken within 24h of extraction. Luckily, progress in optical imaging techniques has meant that SGC function can now finally be studied in vivo, using calcium imaging of dorsal root ganglia (DRG) (Chen, Huang, et al, 2022), the site of peripheral neuron-SGC units.…”
Section: Introductionmentioning
confidence: 99%